Second primary carcinoma arising on a flap: a new primary or a relapse? - Petruzzi, Gerardo; de Bonis, Teodosio; Manciocco, Valentina; Pichi, Barbara; Rosati, Valentina; Iocca, Oreste; Sedran, Luca; Moretto, Silvia; Campo, Flaminia; De Virgilio, Armando; Spriano, Giuseppe; Pellini, Raul (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Free flaps or pedicle flaps are the mainstay of cancer surgery in the head and neck area. However, their long-term sequelae are still poorly understood. Among these, the development of a secondary primary tumor on a flap is a rare and uncertain reported event. Methods: A computer-aided systematic literature search was performed by using the PubMed, EMBASE and Cochrane Library databases. A systematic review of the literature, following the PRISMA checklist, was carried out with the aim of analyzing all the citations reporting this second primary, with attention to risk factors, behavior, etiological causes. Results: Overall, 27 cases of second primary squamous cell carcinoma arising on a pedicle or free flap were identified. In addition, other three cases were discussed. Conclusions: Persistent exposure to oral stimuli such saliva, oral microbiome, smoke or a colonization by the adjacent mucosa were considered as a possible cause of second primary carcinoma. Although rare, a new neoplasm onset should know and considered as a new concept in the follow-up of patients undergoing reconstruction with free or pedicle flaps.